A description of the current status of chronic fatigue syndrome and associated factors among university students in Wuhan, China - Luo, Lunbing; Zhang, Yutong; Huang, Tao; Zhou, Fang; Xiong, Change; Liu, Yang; Zhai, Piyong; Wang, Guiping; Tan, Jianhua; Jiao, Chengjun; Chen, Xin; Yu, Jiao; et al. (Frontiers in Psychiatry, 2023)
The aim of this study is to understand the development status of myalgic encephalomyelitis/chronic fatigue syndrome(ME/CFS) in university students, explore its influencing factors, and provide a theoretical basis for the subsequent intervention and treatment of patient with ME/CFS. A cross-sectional study was conducted among university students in a university in Hubei province. Data were collected via online questionnaire surveys. The contents included demographic characteristics, lifestyles, disease history, depression, anxiety, sleep, ME/CFS and other associated factors. SAS 9.4 statistical software was used to analyze and estimate the effect of associated factors on ME/CFS.A total of 1826 subjects were included in the final analysis. The results showed that the prevalence of ME/CFS in university students was 6.25%. Univariate analysis showed that exercise, alcohol consumption, study, overnights, diet, anxiety, depression, and sleep quality were associated with ME/CFS (P＜0.05). Multivariate analysis showed that overnights, overeating, anxiety, and sleep quality were independent risk factors, while learning was a protective factor. It was concluded that enough attention should be paid to ME/CFS among university students to increase knowledge and awareness about it and improve people’s ability to recognize it.